The rarest of rare mango in Malihabad: Three hundred genotypes of mango scion grafted in a single tree - Sthapit, B. (2011)
Over the years, farmers have developed a range of production and management practices to conserve and sustainably use tropical fruit species diversity in Asia and elsewhere. These good practices can either be farmers’ own innovations or developed by formal research agencies and further adapted by farming community in their own context. Because of perennial nature of the tropical fruit tree crops, research on these crops tends be a long term and costly.Multiple varieties of mango maintenance in a single tree could be a good practice for scion maintenance for those nurseries and field genebank who have limited land resources and staff. Farmer Haji Kaleem Ullaj Khan is well renowned in India for his skills and knowledge in multiple grafting on a single tree.